Space as a Structure Defined by User’s Presence - Szrajber, Rafał (Replay. The Polish Journal of Game Studies, 2019)
The article will discuss issues that show the connection between the culture of video games and its accompanying technology in relation to space – its functionality and ways of shaping, as an area requiring not only research and protection, but even rescue actions to preserve. The space in which technology defines a function or introduces changes to the way the space is used, whether in terms of public or private space, is due to rapid technological changes a heritage area of a very transient nature. Each type of existential space inhabited by man, especially accompanying the development of technology, is a record of contemporary culture which is directly related to the life cycle of technology – short-lived and fleeting, requiring current research and documentation. The article presents, apart from indicating a area of research, theories of layers of modernity – a way of describing individual experience and awareness of the heritage of technology and culture through the prism of the accompanying technologies defining human functioning.